POLITIK HUKUM PEMBERIAN ASIMILASI DI RUMAH BERDASARKAN PERMENKUMHAM NO. 10 TAHUN 2020 (Studi Kasus di Lapas Perempuan Kelas IIA Malang) (Jurnal Magister Hukum Perspektif, 2020)
The above theme taking is motivated by the policy of assimilation of prisoners in the midst of the COVID-19 pandemic, namely the Regulation of the Minister of Law and Human Rights of the Republic of Indonesia Number 10 of 2020 concerning Conditions for Providing Assimilation and Integration for Prisoners and Children in the Framework of Prevention and Countermeasures of the Spread of COVID-19. Assimilation is granted as an inmate's right after fulfilling the conditions in the applicable law. Assimilation is the fostering of adult and child inmates by allowing them to live mingling in the community. The formulation of the issue raised is "What is the legal politics of assimilation at home according to Permenkumham RI Number 10 of 2020 in The Women's Prison Class IIA Malang?". The method used is empirical juridical with a sociological approach. This research seeks to describe the implementation of Permenkumham Number 10 of 2020 in people's lives. Primary data collection is done by interview while secondary data is obtained from library studies and documents related to research problems. The results were found that the implementation of assimilation and integration related to COVID-19 at the Malang Class IIA Women's Prison was in accordance with existing regulations, and was carried out in accordance with established implementation procedures. The reason for providing COVID-19-related assimilation and integration is that inmates and children must meet administrative and substantive requirements. This policy cannot be granted if the inmate and the criminal child do not meet one or both of these conditions. The legal politics of Permenkumham Number 10 of 2020 are very suitable to be applied in the midst of the COVID-19 pandemic because it is a proof of appreciation for human rights. In addition, the interview results also proved that there were no allegations of irregularities or abuses that led to corruption for the implementation of the policy in the Class II Women's Prison A Malang. Keywords: Political Law, Assimilation, Permenkumham Number 10 of 2020.